Examining the mediating effects of motivation between job insecurity and innovative behavior using a variable-centered and a person-centered approach - Ma, Bing; Zhou, Yarong; Lassleben, Hermann; Ma, Guimei; Yang, Rong (Frontiers in Psychology, 2023)
Using a variable-centered approach, this study aims to examine the mediating effects of intrinsic and impression management motivation in the relationship between quantitative and qualitative job insecurity and innovative behavior, including proactive and reactive innovative behavior. In addition, a person-centered approach is used to investigate whether it is possible to distinguish different combinations of quantitative and qualitative job insecurity, and examine the effect of these job insecurity profiles on motivation and innovative behavior. AMOS 24.0 was used to test the hypothesized model and Mplus 8.0 was used to explore the profiles of job insecurity using latent profile analysis. Using 503 data sets collected via the Credamo platform in China, the study found that quantitative job insecurity affects proactive and reactive innovative behavior through impression management motivation and that qualitative job insecurity affects proactive and reactive innovative behavior through intrinsic and impression management motivation. In addition, three job insecurity profiles were identified: balanced high job insecurity, balanced low job insecurity, and a profile dominated by high quantitative job insecurity, all of which have significantly different effects on motivation and innovative behavior, thus compensating for the limitation of the traditional variable-centered approach that cannot capture heterogeneity within the workforce. This study contributes to provide new insights into the relationship between job insecurity and innovative behavior.